Non-motor symptoms in patients with Spinocerebellar ataxia type 12 - Basu, Purba; Choudhury, Supriyo; Mondal, Siddhartha Sankar; Siddique, Ummatul; Rahman, Simin; Ganguly, Jacky; Mukherjee, Soumava; Singh, Nilam; Tiwari, Mona; Kumar, Hrishikesh (Frontiers in Neurology, 2024)
Introduction: Spinocerebellar ataxia type 12 (SCA12) is a rare autosomal dominant neuro degenerative disorder caused by CAG repeat expansion in PPP2R2B gene. The disease is classically characterized by action tremor, dysarthria, ataxia, and hyperreflexia. There are limited reports about nonmotor features in SCA 12. We investigate frequency and factors associated with selected nonmotor symptoms in SCA 12. Methods: Genetically diagnosed (CAG repeats > 43) and symptomatic cases with SCA 12 were included in the study. Motor severity was assessed using Scales for the Assessment and Rating of ataxia (SARA) and The Essential Tremor Rating Assessment Scale (TETRAS). Non motor rating for depression, autonomic function and cognition was performed with Hamilton Depression Rating scale (HAM-D), Scales for Outcomes in Parkinson's Disease -Autonomic Dysfunction (SCOPA-AUT) and Montreal Cognitive Assessment Scale (MoCA) respectively. Results: The mean age in years for 34 SCA12 patients was 64.87 (standard deviation 6.844 ). Twenty-one patients (61.76%) had mild or moderate cognitive impairment, almost equally frequent in early and advanced cases. Same number of patients demonstrated evidence of moderate or severe depression. SARA score was strongly associated with MoCA score and CAG repeat length could independently predict MoCA in this cohort. Autonomic symptoms were commonly present, with the majority suffering from urinary symptoms. Discussion: Nonmotor symptoms are common in SCA12 patients, even in their early stages. Timely detection and treatment of these symptoms may improve the therapeutic outcome and quality of life of SCA12 patients. These diverse symptoms perhaps indicate widespread neurodegeneration beyond cerebellum or its direct connections.